2014
DOI: 10.1080/17518253.2014.927534
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of homogeneous and heterogeneous Ga(III) catalysis in the cycloisomerization of 1,6-enynes

Abstract: We describe a study of the gallium(III)-catalyzed 1,6-enynes cycloisomerization reaction in both homogeneous and heterogeneous conditions. With GaBr 3 in homogeneous conditions, some particularities were observed in terms of selectivity compared to reported GaCl 3-catalyzed reactions. The transfer of the reaction in heterogeneous conditions was realized by supporting Ga(III) salts onto montmorillonite. Both systems were compared based on reaction times, conversion, and selectivity and showed complementary acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…In any case, its starts with the activation of the alkyne moiety, which gains a vinyl carbocation character, triggering an exo - or endo -nucleophilic attack of the alkene. While this chemistry is often regarded as the territory of late-transition-metal-based Lewis acid catalysis, especially gold and platinum, main-group-metal complexes, mostly gallium­(III) and indium­(III) halides, have also been used to promote skeletal reorganization of enynes, including enyne metathesis . Chatani et al reported in 2002 the first examples of GaCl 3 -catalyzed enyne metathesis, as shown in Scheme , eq 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In any case, its starts with the activation of the alkyne moiety, which gains a vinyl carbocation character, triggering an exo - or endo -nucleophilic attack of the alkene. While this chemistry is often regarded as the territory of late-transition-metal-based Lewis acid catalysis, especially gold and platinum, main-group-metal complexes, mostly gallium­(III) and indium­(III) halides, have also been used to promote skeletal reorganization of enynes, including enyne metathesis . Chatani et al reported in 2002 the first examples of GaCl 3 -catalyzed enyne metathesis, as shown in Scheme , eq 1 .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 We previously reported the use of MMT-supported gallium species as a catalyst for 1,6enynes cycloisomerisation. 29 The catalysts were prepared by impregnation of solutions of sustainable metal salts such as BiCl 3 , FeCl 3 , and CuCl 2 in MeOH. Under an inert atmosphere, 10 mmol of an anhydrous precursor was added to 10 g of pre-lyophilised MMT and 50 mL of MeOH.…”
mentioning
confidence: 99%
“…h Pores of less than 102 nm at P/P 0 0.98. i Pores of less than 1.5 nm at P/P 0 of 0.1. j Pores of less than 95 nm P/P 0 of 0.98. k Pores of less than 1.56 nm at P/P 0 of 0.1. tions. 5,6,44,57 Moreover, it was shown that the heterogeneous catalyst derived from the POPs was much more selective than the homogeneous catalyst model. This fact could be explained by the confinement effect of the catalyst inside the pores of the material.…”
Section: Characterization Of the Au I Carbene Pop Catalysts (Pop-auca...mentioning
confidence: 99%
“…56 These results, added to the easy recovery of the catalyst, are a promising solution to green and sustainable development in the chemical industry. 5,6,17,30,57 In this work, we report the formation of a catalytic Au I material where a NAC has been confined into microporous polymer networks. POPs have shown great efficiency as heterogeneous catalysts, thanks to properties such as their high microporosity, and when a polymer material has been chosen, they show excellent thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation